2017
DOI: 10.4103/0971-4065.194393
|View full text |Cite
|
Sign up to set email alerts
|

Innominate vein stenosis in association with ipsilateral hyperdynamic brachiobasilic fistula causing ipsilateral limb and hemifacial swelling

Abstract: A 34-year-old hypertensive woman with a hyperdynamic, left brachiobasilic dialysis fistula presented with a long history of throbbing in her head and swelling of the left side of the face. Tight stenosis of left brachiocephalic vein was found to be causing retrograde flow into the left jugular vein which normalized after dilatation and stenting with resolution of all the symptoms and patient is asymptomatic for 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
2
2
0
Order By: Relevance
“…The association between patient demographics and the onset of central vein disease has not been well substantiated in literature, and sex, age, and comorbidities are possible prognostic variables that may predict disease progression. 16 Sex distribution was comparable in our study, whereas other earlier studies reported that women were more susceptible to CVL development than men. 16 18 Further, age at hemodialysis initiation was reported to provide a more comprehensive picture of the distribution of lesion onset.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…The association between patient demographics and the onset of central vein disease has not been well substantiated in literature, and sex, age, and comorbidities are possible prognostic variables that may predict disease progression. 16 Sex distribution was comparable in our study, whereas other earlier studies reported that women were more susceptible to CVL development than men. 16 18 Further, age at hemodialysis initiation was reported to provide a more comprehensive picture of the distribution of lesion onset.…”
Section: Discussionsupporting
confidence: 68%
“… 16 Sex distribution was comparable in our study, whereas other earlier studies reported that women were more susceptible to CVL development than men. 16 18 Further, age at hemodialysis initiation was reported to provide a more comprehensive picture of the distribution of lesion onset. 2 The mean age of patients at hemodialysis initiation in our study was 51.9 ± 14.9 years, which was found consistent with the age ranges reported in other studies.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations